24‐2: Distinguished Paper: Achieving a Foldable & Durable OLED Display with BT.2020 Color Space using Innovative Color Filter Structure. Issue 1 (2nd June 2017) - Lee, Meng-Ting; Wang, Cheng-Liang; Chan, Chi-Shun; Fu, Ching-Chieh; Shih, Ching-Yao; Chen, Chung-Chia; Lin, Kuan-Heng; Chen, Yi-Hong; Su, Wei-Jen; Liu, Chia-Hsing; Ko, Chien-Ming; Weng, Zai-Xien; et al.
Abstract : A foldable AMOLED display capable of enduring very severe folding and environmental impact was obtained using symmetric panel stacking (SPS) with an innovative design of color filter structure. The display was subjected to in‐situ folding cycle under an ambient test condition of 60° C/90% RH and no performance degradation was found for the display and the touch function during and after the test. In addition, 95% coverage of BT. 2020 color space was obtained without additional power consumption compared to that of the panel with NTSC color space.